2016
DOI: 10.1038/nature20569
|View full text |Cite
|
Sign up to set email alerts
|

Accessing non-natural reactivity by irradiating nicotinamide-dependent enzymes with light

Abstract: Enzymes are ideal for use in asymmetric catalysis by the chemical industry, because their chemical compositions can be tailored to a specific substrate and selectivity pattern while providing efficiencies and selectivities that surpass those of classical synthetic methods. However, enzymes are limited to reactions that are found in nature and, as such, facilitate fewer types of transformation than do other forms of catalysis. Thus, a longstanding challenge in the field of biologically mediated catalysis has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
203
0
12

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 328 publications
(237 citation statements)
references
References 29 publications
5
203
0
12
Order By: Relevance
“…Ketoreductase activity was transformed into an initiator of radicals and a source of 'chiral' hydrogen atoms. This occurred on irradiation of the nicotinamide cofactor and led to enantioselective dehalogenation of racemic halolactones 85 . In a second example, the scope of this electron transfer capability was recently expanded to ene-reductases 86 .…”
Section: Novel Chemistries and Other Trendsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ketoreductase activity was transformed into an initiator of radicals and a source of 'chiral' hydrogen atoms. This occurred on irradiation of the nicotinamide cofactor and led to enantioselective dehalogenation of racemic halolactones 85 . In a second example, the scope of this electron transfer capability was recently expanded to ene-reductases 86 .…”
Section: Novel Chemistries and Other Trendsmentioning
confidence: 99%
“…Recently, Jeschek et al demonstrated the power of the streptavidin concept by developing a Hoveyda-Grubbs second-generation Ru catalyst containing metalloenzyme for in vivo metathesis in the periplasm of E. coli 84 . A similar strategy for accessing non-natural enzyme activity, via application of a natural cofactor, was utilized by Hyster 85,86 . Ketoreductase activity was transformed into an initiator of radicals and a source of 'chiral' hydrogen atoms.…”
Section: Novel Chemistries and Other Trendsmentioning
confidence: 99%
“…Nicotinamide‐dependent enzymes are not known to act as photoenzymes under natural conditions but can be used as such and thereby mediate novel reactions. As an example, ketoreductase can be transformed from a carbonyl reductase into an enzyme that produces chiral lactones instead of alcohols from racemic lactones (Fig. ).…”
Section: Nicotinamide‐dependent Enzymes As Photoenzymesmentioning
confidence: 99%
“…[1] In contrast to traditional organometallic catalysts,they offer attractive alternatives due to their low toxicity and mild reaction conditions.H owever,i nm ost cases, enzymes catalyze only their respective natural reaction types.I nducing additional reactivities,r esulting in enzymatic promiscuity,r emains ag reat challenge. [3][4][5][6] Fore xample,n icotinamide-dependent ketoreductases were employed to catalyze asymmetric dehalogenation by irradiating with light. [3][4][5][6] Fore xample,n icotinamide-dependent ketoreductases were employed to catalyze asymmetric dehalogenation by irradiating with light.…”
mentioning
confidence: 99%